(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article analyzes the pedagogical foundations of training informatics teachers for independent research activity. Guiding students to independent work and research, increasing their activity in the educational process and developing the ability to think independently are important parts of the modern educational process. Effective organization of independent research activity plays an important role in the application of students’ theoretical knowledge in practice. The article discusses methods of involving students in independent work, describes types of independent activity, and the importance of modern pedagogical technologies for the effective organization of this process. It also discusses the difficulties encountered in organizing independent research activity and gives recommendations for their elimination. Through independent activity, students have the opportunity to develop creative thinking, critical thinking, and self-development skills.